Algorithmic and Experimental Methods in Algebra, Geometry, and Number Theory - Böckle, Gebhard; Decker, Wolfram; Malle, Gunter (Springer, 2017)
Introduction -- Bächle et al: Algorithmic aspects of units in group rings -- M. Barakat et al: A constructice approach to the module of twisted glocal sections on relative projective spaces -- J. Böhm et al: Local to global algorithms for the Gorenstein adjoint ideal of a curve -- M. Börner et al: Picard curves with small conductor -- W. Bruns et al: Normaliz 2013-2016 -- T. Centeleghe et al: Integral Frobenius for abelian varieties with real multiplication -- M. Dettweiler et al: Monodromy of the multiplicative and the additive convolution -- B. Eick et al: Constructing groups of ‘small’ order: Recent results and open problems -- B. Eick et al: Classifying nilpotent associative algebras: small coclass and finite fields -- A. Fruehbis-Krüger et al: Desingularization of arithmetic surfaces: algorithmic aspects.- A. Gathmann et al: Moduli spaces of curves in tropical varieties -- A. Gathmann et al: Tropical moduli spaces of stable maps to a curve -- M. Geck et al: Invariant bilinear forms on W-graph representations and linear algebra over integral domains -- S. Hampe et al: Tropical computations in polymake -- M. Hoff: Focal schemes to families of secant spaces to canonical curves -- T. Hoge et al: Inductive and recursive freeness of localizations of multiarrangements -- L. Kastner: Toric ext and tor in polymake and Singular: The twodimensional case and beyond -- M. Lange-Hegermann et al: The differential dimension polynomial for characterizable differential ideals -- V. Levandovskyy: Factorization of Z-homogeneous polynomials in the first q-Weyl algebra -- E.W. Mayr et al: Complexity of membership problems of different types of polynomial ideals -- T. Moeller et al: Localizations of inductively factored arrangements -- G. Nebe et al: One class genera of lattice chains over number fields -- A. Paffenholz: polyDB: A database for polytopes and related objects -- G. G. Pfister et al: Construction of neron desingularization for two-dimensional rings. - T. Rossmann et al: A framework for computing zeta functions of groups, algebras, and modules -- A. Shalile: On decomposition numbers of diagram algebras -- U. Spreckels et al: Koblitz’ conjecture for abelian varieties -- M. Stoll: Chabauty without the Mordell-Weil group -- M. Stoll: An explicit theory of heights for hyperelliptic Jacobians of genus three -- T. Theobald: Some recent developments in spectrahedral computation -- G. Wiese et al: Topics on modular Galois representations modulo prime powers